ANALISIS PENERAPAN KETERAMPILAN MEMBUKA PELAJARAN OLEH GURU SOSIOLOGI KELAS XA - Aulia, Ivan; Budjang A, Gusti; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this thesis is "Analysis of the Application of Opening Skills of Teaching by Sociology Teachers of Class XA of SMA PGRI 1 PONTIANAK". The purpose of this study is to describe the application of the skills to open teacher learning at PGRI 1 Pontianak High School. This researcher was carried out using descriptive research methods using qualitative forms. The research technique used is 1. Direct Communication Technique and 2. Documentary Study Technique. From the results of the study can be concluded as follows: 1) Skills to open lessons to cause students' motivation in sociology subjects in class X a SMA 1 PGRI Pontianak, based on the results of research observations and interviews are quite skilled. 2) The results of the observation showed that the teacher applied the skills to open the lesson in attracting the attention of students in the sociology subject of class X a SMA1 PGRI Pontianak quite skillfully carried out can be categorized as "Good" in this case seen from the teacher's skill in applying the skills to open the lesson in attracting students' attention, motivating students and provide references in learning.Â Keyword : Learning Skills, High School Teachers.